Low-Cost CSRR-based Microwave Sensor for Evaluating Water Quality to Prevent Unwanted Sugar Contamination - Bruno Matias de Sousa; José Garibaldi Duarte Júnior; Valdemir Praxedes da Silva Neto (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract This study proposes a low-cost microwave sensor for the monitoring of water quality contamination in irrigation systems. The sensor was employed for monitoring the concentration of specific compounds in mixtures of glucose and water, in order to prevent the accumulation of unwanted sugars in large plantations. The proposed sensor is an adaptation of a complementary split ring resonator (CSRR) fabricated on an FR4 substrate. A capillary tube constructed from polypropylene is inserted into the region of the CSRR microwave sensor exhibiting the maximum density surface current, wherein the liquid under test (LUT) is contained. The sensor was designed to operate at a resonance frequency of 2.45 GHz in the absence of a load. The maximum displacement observed at the resonance frequency is 275 MHz, with a normalization sensitivity of 0.844%. The simulations and experimental measurements are verified and their results compared, yielding a high level of concordance for the sensor’s intended purpose. The discrepancy between the measured permittivity values and the reference values of the samples under analysis is less than 5%. The proposed sensor is an effective solution for characterizing liquids, particularly mixtures of water and glucose, when compared to other sensors available for this application